Nation - Pratchett, Terry (New York : HarperCollins, 2008)
A tsunami destroys everything leaving Mau, an island boy, Daphne, an aristocratic English girl, and a small group of refugees responsible for rebuilding their village and their lives.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
Booklist starred, August 2008.
Horn Book Starred, September 2008.
Horn Book, April 2009.
Keywords: Interpersonal relations -- Juvenile fiction; Survival -- Juvenile fiction; Tsunamis -- Juvenile fiction; Interpersonal relations -- Fiction; Survival -- Fiction; Tsunamis -- Fiction; Interpersonal relations -- Fiction; Survival skills -- Fiction; Tsunamis -- Fiction